Spatial variation of rainfall in the Medina region for the period (1985 – 2020) - Al-Sahli, Najwa Mounir; Buqiri, Fayidah Kamil (Journal of Humanities & Social Sciences, 2024)
This research is concerned with studying the spatial and temporal variation of rainfall characteristics in the Medina region for the period from 1985-2020 AD.), due to the location of the region in the dry tropical zone, which is characterized by scarcity and fluctuation of rainfall spatially and temporally. This research aims to identify the spatial and temporal variations of rainfall in the study area to know and determine the relationship between natural factors and the pattern of rainfall distribution spatially and temporally in the study area. The research relied on the descriptive and analytical approach in studying rainfall characteristics using monthly and annual records of climatic elements data for 15 stations distributed throughout the study area. The importance of this research appears in studying rainfall characteristics in an area with agricultural interests. The research results showed that the distribution of rainfall among parts of the study area is not symmetrical and rainfall rates range between 20.38 - 83.49 mm. The research results also showed that the general trend of rainfall in the study area has taken a decreasing direction during the study period, with the exception of four stations (Adh-Dhulay'ah, Suwaiq, Yanbu, and Al-Masjid). The research recommends the importance of studying the characteristics of rainfall in all stations in the Kingdom of Saudi Arabia.
Keywords: Spatial Variation; Temporal Variation; Rainfall; Al Madinah Region; Climate Change; Arid Tropical Zone